Small mammals (Didelphimorphia and Rodentia) of the archaeological site Calera (Pampean region, Buenos Aires Province, Argentina): Taphonomic history and Late Holocene environments - Scheifler, Nahuel Alberto (2012)
Small mammal (Rodentia and Didelphimorphia) remains were recovered from the archaeological site Calera, Pampean region, Buenos Aires Province, Argentina. This site is located in the upper course of the Arroyo Tapalqué, at the western portion of the Tandilia range system. Calera is formed of a series of transgressive features (pits) that were infilled with faunal, lithic, and ceramic materials. The samples studied here are from Pit 2, with radiocarbon dates of 3008 ± 44 BP (bottom), 3005 ± 66 BP (middle) and 2075 ± 44 BP (top). Sigmodontine rodents are diverse, including at least nine species; also recorded were four caviomorph rodents and one didelphid marsupial. Taphonomical analyses suggest that the remains were mainly accumulated by owls and later transported and reworked by water action. The small mammal assemblage of Calera suggests that the environmental conditions at the beginning of the Late Holocene were similar to the present ones, temperate-humid, or perhaps slightly warmer and/or humid. In overall terms, recorded taxa at Calera are indicative of a mosaic of grasslands, flooded terrains and lentic to lotic water bodies. Noteworthy records are those of the sigmodontine rodents Bibimys cf. Bibimys torresi and Pseudoryzomys simplex, both hundreds of kilometers south of their current ranges. The regional extinction of these two mammals over a large area of central-eastern Argentina is perhaps a very recent event, mostly triggered by human impact.